Fifteen wild Decembers - Powell, Karen (Novelist) (Europa Editions, 2025)
"Isolated from society, Emily Brontë and her siblings spend their days inventing elaborate fictional realms or roaming the wild moors above their family home in Yorkshire. When the time comes for them to venture out into the world to earn a living, each of them struggles to adapt, but for Emily the change is catastrophic. Torn from the landscape to which she has become so passionately bound, she is simply unable to function. To the outside world, Emily Brontë appears taciturn and unexceptional, but beneath the surface her mind is in a creative ferment. A violent phenomenon is about to burst forth that will fuse her imaginary world with the landscape of her beloved Yorkshire and change the literary world forever"--Publisher.